Pengaruh Variasi Campuran Solar Dan Biodiesel Dari Minyak Jelantah Terhadap Sudut Injeksi Dan Dinamika Pembakaran - Rahmadi, Hairian; Soeparman, Sudjito; Pratikto, . (Teknik Mesin "TEKNOLOGI", 2010)
The development of the world today that require the use of renewable energy as fuel non-renewable fossil fuels in particular. Because fossil fuels are declining in number, then needed alternative energy sources as a substitute fuels. As one alternative fuel is biodiesel which is often added in fossil fuels such as biodiesel mixed with diesel fuel. With increasing biodiesel in diesel fuel will increase nilat viscosity, increasing the value of the viscosity of biodiesel in diesel fuel injection will allegedly spreading angle narrows and the dynamics of combustion is expected to affect the dynamics of combustion. This research was conducted with a mix of diesel fuel and biodiesel, with a mixture of 0 *, 20, 40, 60, 80, 100% biodiesel, tested using agricultural machinery YANMAR brand with 10.5 bar pump injector, nozzle 7.5 bar with a diameter of 1 mm , using a dynamo to drive a knock-as to pump injection pump. Angle spread, the dynamics of combustion using a video camera. The results showed that the angle spread narrowed as the increasing percentage of biodiesel in diesel fuel ie from 13.650 to 12.370 on pure biodiesel. fire and high velocity will increase with the addition of biodiesel in diesel fuel. High growth speed of the fire and flames on the percentage of Â biodiesel blend showed the highest high-fire reached with kecepatan 101 cm, 1,3 cm / s, which approximates the high heat and speed of the diesel fuel fire that reached 95 cm and a speed of fire 1.2 cm / sec. Keywords: Biodiesel, diesel fuel, angle of injection, combustion dynamics.